Weak and strong sustainability indicators, and regional environmental resources - Michael Kosz (European Regional Science Association (ERSA), 1998)
Many attempts to operationalize the ecological concept of sustainability have been undertaken by the economics profession during recent years. It seems that many mainstream economists tend to focus their research on the assumption of substitutability between man-made (manufactured) capital and natural capital (natural resources, goods and services). The crucial points of this discussion can be seen especially in contributions by R. Solow (on a more theoretical level) and by R. Atkinson and D. Pearce (on an empirical level) who all plead for at least partial substitutability. As H. Daly has pointed out, the assumption of substitutability cannot be drawn in the search for an adequate treatment of natural resources in economic and ecological modeling and policy. The paper tries to clarify some questions regarding weak and strong sustainability indicators as well as sustainability rules for dealing with regional natural resources. In the first part of the paper, the assumption of substitutability is discussed in various aspects. Given weak sustainability indicators, calculating the ?sustainability" of a regional system (or national economy) becomes almost trivial. If the rate of depreciation of natural capital is at least offset by savings (accumulation) of man-made capital then the economy is on a sustainable development path. Besides the missing of the social ?branch" of sustainability, the depreciation-savings approach lacks understanding of the fundamental objections against monetizing natural resources (e. g. biodiversity). Some crucial aspects in this context are discussed in the paper (e. g. lexicographic preferences, ?consumer"-vs.-?citizen" approach). The strong sustainability indicators are in favor of different approaches, e. g. the save-minimum-approach. The second part of the paper deals with practical sustainability rules on a regional level regarding water resources. If sustainability as a concept for future ecological, economic and social development is taken seriously, only physical constraints (taking time as an additional factor of production into account) and an applied precautionary principle can indeed lead to sustainability. Congress topic: Environmental Management, Sustainability and Development Keywords: Weak/Strong Sustainability Indicators; Regional Indicators for Sustainable Development
Keywords: 330